Species groups in the genus Atrocrates Koch, 1956 (Coleoptera: Tenebrionidae: Pedinini) - Iwan, Dariusz (Zootaxa, 2016)
The genus Atrocrates Koch, 1956 belongs to the trigonopoid evolutionary lineage of the subtribe Platynotina, which consists of endemic South African genera. In the present paper, a division of Atrocrates based on the structure of mentum, pronotum, male mid tibiae, elytral humeri into the following species groups is proposed: bellamyi (10 species), bisinuatus (5), capensis (3), coconatae (5), evestigator (4), formosus (2), galbasi (2), occultator (2). An illustrated key to all of the above mentioned species groups is included. Moreover, two news species A. galbasi sp. nov. and A. matthewsi sp. nov. from Southern Africa are diagnosed, described and illustrated.